Promising Antioxidant and Anticorrosion Activities of Mild Steel in 1.0 M Hydrochloric Acid Solution by Withania frutescens L. Essential Oil - El moussaoui, Abdelfattah; Kadiri, Mariya; Bourhia, Mohammed; Agour, Abdelkrim; Salamatullah, Ahmad Mohammad; Alzahrani, Abdulhakeem; Alyahya, Heba Khalil; Albadr, Nawal A.; Chedadi, Mohamed; Sfaira, Mouhcine; Bari, Amina (Frontiers in Chemistry, 2021)
The present study was undertaken to evaluate the anticorrosive and anti-antioxidant activities of essential oil from Withania frutescens L. In the present study, the extraction of Withania frutescens L essential oil (Wf-EO) was conducted using hydrodistillation before being characterized by gas chromatographic analysis (GC/MS) and flame ionization detector (GC/FID). Four bioassays were used for antioxidant testing including DPPH, TAC, FRAP, and β-carotene bleaching. The inhibiting effect of Wf-EO on the corrosion behavior of mild steel in 1.0 M HCl was conducted by using polarization curves, and electrochemical impedance spectroscopy techniques. The yield of Wf-EO was 0.46% including 175 compounds identified by GC-MS. The oil was mostly constituted of camphor (37.86%) followed by thujone (26.47%), Carvacrol (6.84%), Eucalyptol (3.18%), and linalool (2.20%). The anti-free radical activity of Wf-EO was 34.71±0.91 µg/mL (DPPH), 9.67±0.15 mg/mL (FRAP), 3.78±0.41 AAE/mg (TAC) as well as 89.94±1.44% (β-carotene). The Wf-EO showed potent antioxidant activity in all bioassays used for testing. The anticorrosion activity, polarization curves as well as EIS diagrams indicated that the Wf-EO exhibited anti-corrosive properties and reacted as a suitable corrosion inhibitor in an acidic medium.